Molegro Virtual Docker-Based Prediction of Rhodomyrtus tomentosa Metabolites Targeting Ribonucleotide Reductase as Potential Anticancer Agents - Imam Nurjaman; Dini Kesuma; Tegar Achsendo Yuniarta; Nina Dewi Oktaviyanti (Indonesian Society for Cancer Chemoprevention, 2025)
The increasing number of cancer cases has prompted the search for new drug candidates from natural ingredients, particularly plant-derived compounds considered safer and more effective. Rhodomyrtus tomentosa (Aiton) Hassk. contains various metabolites responsible for various biological activities. This study aimed to predict the anticancer potential of R. tomentosa metabolites against the Ribonucleotide Reductase (RNR) enzyme using an in silico approach. The RNR protein structure (PDB ID: 2WGH) was obtained from the RCSB Protein Data Bank. Molecular docking was performed on 25 compounds previously reported in the literature as metabolites of R. tomentosa using Molegro Virtual Docker (MVD) version 7.0 to evaluate ligand-receptor binding affinity based on MolDock Score values using a validated docking protocol (RMSD≤2.0 Å), followed by interaction analysis and pharmacokinetic evaluation using ADMET parameters. The results indicated that most compounds exhibited favorable binding affinities toward RNR, as reflected by negative MolDock Score values. Rhodomyrtosone B (−137.144 kcal/ mol) showed the best binding affinity, followed by Malvidin-3-glucoside (−135.173 kcal/ mol), Delphinidin-3-galactoside (-132.359 kcal/mol), Rhodomyrtosone I (−130.004 kcal/ mol), and Cyanidin-3-galactoside (-127.741 kcal/mol). Interaction analysis revealed stable interactions with key amino acid residues (Arg256, Asp226, and Ser269) through hydrogen bonding, hydrophobic, and electrostatic interactions. ADMET analysis indicated variability in pharmacokinetic properties, including absorption, distribution, metabolism, and toxicity. In conclusion, Rhodomyrtosone B has potential as a natural product-based anticancer agent targeting RNR, providing a basis for further in vitro and in vivo studies.Keywords: anticancer, Rhodomyrtus tomentosa, molecular docking, Ribonucleotide Reductase; in silico.